A review of TiO2 nanostructured catalysts for sustainable H2 generation. (23rd March 2017) - Ge, Mingzheng; Cai, Jingsheng; Iocozzia, James; Cao, Chunyan; Huang, Jianying; Zhang, Xinnan; Shen, Jiali; Wang, Shanchi; Zhang, Songnan; Zhang, Ke-Qin; Lai, Yuekun; Lin, Zhiqun
Abstract: Hydrogen is an attractive alternative to fossil fuels that addresses several environmental and energy shortage issues. Nano-sized TiO2 -based photocatalysts with unique structural and functional properties are the most extensively studied photocatalytic nanomaterials for hydrogen production and pollutant degradation. However, titania is hampered by a wide band gap, low utilization of solar light and a rapid recombination of electron/hole pairs. These issues limit its photocatalytic performance. In this review, we present the latest developments in the fabrication of different higher dimensional TiO2 nanostructured materials that aim to address these inherent limitations to an otherwise very promising material. Specifically, we will look into critical engineering strategies to enlarge the active surface area, enhance visible light absorption and suppress the recombination of electrons/holes that benefit their photo/photoelectric-catalytic water splitting activity. Finally, the current challenges and perspectives for TiO2 nanostructures are also discussed. Continuous efforts are necessary to endow TiO2 -based materials with novel advanced functionality and commercialization potential in the coming years. Graphical abstract: The state-of-the-art development of fabrication method on 0D, 1D, 2D and 3D TiO2 nanostructures is reviewed first. And then we will look into some critical engineering strategies to enlarge the active surface area, enhance visible light absorption and suppress the recombination of electrons/holes that benefit their photo/photoelectro-catalytic water splitting activity. Highlights: State-of-the-art development on the fabrication of various TiO2 materials is reviewed. Heterogeneous structures are designed by various strategies for enhanced H2 O splitting activity. Challenge and perspective on TiO2 materials are stated for efficient H2 production.